Application of Pore Network Modelling Techniques for Evaluating the Performance of Coalescing Filters - Azarafza, Abouzar (Curtin University, 2021)
During his PhD work, Abouzar has developed a more computationally efficient approach using dynamic pore network model to improve the design and operation of liquid coalescing filters. The modeling technique was used to study key phenomena and to optimize filter performance. Several important advantages of the proposed model over currently-available modelling approaches were demonstrated. It was shown that the novel modelling technique could be used as a promising tool for designing of mist filters.